From the Voice to the Violent Act: Language and Violence in Contemporary Drama - Bryan, Richard A. (2006)
Aleks Sierz coined the phrase In-Yer-Face Theatre to categorize a new generation of plays written by a group of upstart playwrights in Britain and America. In addressing these plays, I draw upon recent contributions within the social sciences in order to understand better the interstices of language and violence in this drama. This interdisciplinary approach underscores the social considerations at the heart of these plays. Although frequently criticized for a perceived lack of social consciousness and a seemingly gratuitous use of profanity, prurient sexuality, and graphic violence, these writers in fact continue, and contribute to, a tradition of theater that is serious, ethically based, and socially aware. Specifically, the language represented in these plays is symptomatic of, and complicit in, the violence depicted on stage. I first argue that coercive institutional language subjects the characters in David Mamet's 0leanna to systematic violence long before the infamous moment of violence that concludes the play. The reifying language of consumer capitalism in the plays of Patrick Marber and Mark Ravenhill precipitates violence by rewriting the cultural codes that inform subjectivity and the way that interpersonal relationships are conceived and experienced. Examining the work of David Harrower, Bryony Lavery, David Eldridge, and Tracy Letts, I identify examples of public language and show how they hamper intellectual development and maturity and disengage the cognitive mechanisms that allow individuals to regulate their behavior. I explore the allegiance on the part of those in subcultures of violence to the heavily gendered constructions of identity facilitated by their subcultural languages, and I address the linguistic mechanisms by which the characters in Rebecca Prichard's Fair Game create the sense that violence is necessary. In addition, I interrogate the formal nature of hyper-masculine violence. Finally, in the plays of Martin McDonagh, Judy Upton, and Rebecca Prichard, I discuss the adoption of traditionally male forms of violence by women, focusing on language's role in determining the likelihood and the nature of the violence committed both by and against women